THE APPLICATION OF SCRAMBLE METHOD USING MULTIMEDIA FOR IMPROVING SCIENCE LEARNING FOR THE FIFTH GRADE STUDENT OF SDN PASIR WETAN IN THE ACADEMIC YEAR OF 2014/2015 - Rosiana, Helmina (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Scramble Method Using Multimedia for Improving Science Learning for The Fifth Grade Student of SDN Pasir Wetan in The Academic Year of 2014/2015. The aims of this research to describe the steps of application of scramble method using multimedia, to improving science learning about the process of soil formation and to describe the problems and solution of using of scramble method using multimedia. This classroom action research was conducted in three cycles, consisting of planning, implementation, observation, and reflection. The result of the research show that application of scramble method using multimedia can improve science learning. The percentage of completeness was 73,68% in the first cycle, 86,84% in the second cycle, and 94.74% in the third cycle. The conclusion of this research is the application of scramble method using multimedia can improve science learning for the fifth grade of SDN Pasir Wetan in the academy year of 2014/2015. Keyword: Scramble Method, Multimedia, Science Learning Abstrak: Penggunaan Metode Scramble dengan Multimedia dalam Peningkatan Pembelajaran IPA pada Siswa Kelas V SDN Pasir Wetan Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk mendeskripsikan langkah-langkah penggunaan metode scramble dengan multimedia, meningkatkan pembelajaran IPA tentang pembentukan tanah serta mendeskripsikan kendala dan solusi penggunaan metode scramble dengan multimedia. Penelitian Tindakan Kelas dilaksanakan dalam tiga siklus terdiri atas perencanaan, pelaksanaan, pengamatan, refleksi. Hasil penelitian menunjukkan penggunaan metode scramble dengan multimedia dapat meningkatkan pembelajaran IPA. Persentase ketuntasan siswa pada siklus I sebanyak 73,68%, siklus II %,86,84 dan siklus III 94,74%. Simpulan penelitian ini adalah penggunaan metode scramble dengan multimedia dapat meningkatkan pembelajaran IPA pada siswa kelas V SDN Pasir Wetan tahun ajaran 2014/2015. Kata Kunci: Metode Scramble, Multimedia, Pembelajaran IPA